Public Speaking in Academic Context: A Study of Student Communication Obstacles and Strategies - Wika Wahyuni; I Nyoman Sudika; Pipit Aprilia Susanti; Januari Rizki Pratama; Yuniar Nuri Nazir; Septi Rizkia (Jurnal Ilmiah Mandala Education (JIME), 2025)
Public speaking is one of the most important skills for students. Public communication skills not only play a role in supporting academic success, but also provide great benefits in professional and social life. In fact, it turns out that many students still experience obstacles when they have to speak in front of many people, including in academic presentations. Based on these facts, this study attempts to classify the obstacles to public communication of students so that recommendations can be provided to overcome these obstacles to public communication in the campus environment. Data were collected using observation and interview methods. Furthermore, the data were analyzed using the content analysis method and presented informally. The findings of this study are several obstacles to public communication, namely linguistic, psychological, technical, environmental, body movement, mastery of material, and visual aids. From these findings, it is concluded that the obstacles to public communication in students' academic presentations mostly come from internal factors (linguistic, psychological, body movement, and mastery of material) and external factors (technical, visual aids, and environmental). Students who are less accustomed to public speaking tend to have difficulty organizing material and delivering it well. In addition, the lack of training in the use of presentation aids worsens the situation